FOODSERVICE OPERATIONS AND MANAGEMENT Concepts and Applications - Drummond, Karen Eich; Cooley, Thomas J.; Cooley, Mary (Jones & Bartlett Learning, 2022)
Foodservice Operations & Management: Concepts and Applications is written for Nutrition and Dietetics students in undergraduate programs to provide the knowledge and learning activities required by ACEND's 2017 Standards in the following areas: Management theories and business principles required to deliver programs and services. Continuous quality management of food and nutrition services. Food science and food systems, environmental sustainability, techniques of food preparation and development and modification and evaluation of recipes, menus, and food products acceptable to diverse populations. (ACEND Accreditation Standards for Nutrition and Dietetics Didactic Programs, 2017) The textbook can also be used to meet the competencies in Unit 3 (Food Systems Management) and Unit 5 (Leadership, Business, Management, and Organization) in the Future Education Model for both bachelor's and graduate degree programs.